1988
DOI: 10.1007/bf00930896
|View full text |Cite
|
Sign up to set email alerts
|

The social supports of suicide attempters: The different roles of family and friends

Abstract: The social support patterns of a sample of 101 suicide attempters were compared with the patterns of a control sample on the basis of structured interview data. Network characteristics and the extent of support in different functional categories were examined as to their absolute and relative power to discriminate between the suicide attempters and the controls. A clear separation of the functions of kin and of friends/acquaintances emerged. The crucial difference between the attempters and the controls lay in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
3

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 30 publications
4
22
0
3
Order By: Relevance
“…Hereby, it was decided to focus on life events that have repeatedly been found to be associated with attempted suicide and that reflect a threat to the quality of a person's interpersonal network. This choice was made because studies have repeatedly found that social isolation is a risk factor for suicide and that social support is a protection factor for suicide (Veiel, Brill, Haefner, & Welz, 1988). In agreement with the previous research, we expected experiences of (types of) traumatic life events to be more common among suicidal inmates than among nonsuicidal inmates (Hypothesis 1) and suicidal inmates to have experienced more traumatic life events during childhood, later life, and detention than nonsuicidal inmates (Hypothesis 2).…”
supporting
confidence: 60%
“…Hereby, it was decided to focus on life events that have repeatedly been found to be associated with attempted suicide and that reflect a threat to the quality of a person's interpersonal network. This choice was made because studies have repeatedly found that social isolation is a risk factor for suicide and that social support is a protection factor for suicide (Veiel, Brill, Haefner, & Welz, 1988). In agreement with the previous research, we expected experiences of (types of) traumatic life events to be more common among suicidal inmates than among nonsuicidal inmates (Hypothesis 1) and suicidal inmates to have experienced more traumatic life events during childhood, later life, and detention than nonsuicidal inmates (Hypothesis 2).…”
supporting
confidence: 60%
“…Elle montre que les hommes qui ont fait une tentative de suicide perçoivent moins de soutien social disponible dans leur réseau que les hommes sans antécédent suicidaire, et ce, même lorsqu'on contrôle statistiquement l'effet des troubles mentaux et de l'absence d'un partenaire amoureux. Ces résultats vont dans le même sens que ceux rapportés dans des études précédentes (Botnick et al, 2002 ;Eskin, 1995 ;Lewinsohn et al, 1993 ;Sokero et al, 2003 ;Veiel et al, 1988). Toutefois, contrairement à ces études, nous n'observons aucune différence entre les groupes quant à la taille du réseau de soutien.…”
Section: Discussionunclassified
“…Plusieurs chercheurs ont tenté de vérifier s'il en était de même pour les comportements suicidaires. Les études indiquent généralement que les personnes qui ont fait une tentative de suicide perçoivent moins de soutien disponible dans leur entourage que les personnes sans antécédent suicidaire (Botnick et al, 2002 ;Eskin, 1995 ;Lewinsohn et al, 1993 ;Sokero et al, 2003 ;Veiel et al, 1988), bien qu'une telle différence ne soit pas toujours rapportée (Kotler et al, 1993 ;Mullis et Byers, 1987). Le soutien social pourrait protéger des comportements suicidaires, mais les mécanismes par lesquels s'exerce cette influence protectrice sont méconnus.…”
Section: Résumé De L'articleunclassified
See 1 more Smart Citation
“…In non-clinical studies, several dim ensions of social support have been identi® ed as correlates of suicide attempt: sm all non-fam ily social networks (Veiel et al, 1988), perception of the social network as unavailable or inadequate (Hart et al, 1988;Lyons, 1985), im paired social integration (BilleBrahe & W ang, 1985), low er levels of instrumental support and psychological support from fam ily (Veiel et al, 1988) and low levels of subjective support (H art et al, 1988). Low scores on a cum ulative social support m easure in inpatients admitted following a suicide attem pt predicted increased risk of reattem pt in a longitudinal study by Johnsson F ridell et al (1996).…”
Section: G Oals Of the Studymentioning
confidence: 98%